PENINGKATAN HASIL BELAJAR DAN KREATIFITAS PESERTA DIDIK PADA MATERI BANGUN DATAR MENGGUNAKAN MODEL PROJECT BEST LEARNING (PJBL) DI SDN 2 BETENG KOTA KLATEN - isnawati, Indriana (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This research aims to improve the learning outcomes and creativity of class I students at SD Negeri 2 Beteng, Jatinom, Klaten Regency, in Mathematics subjects with flat shapes material using the Project Based Learning (PBL) method. The research uses a Classroom Action Research (PTK) approach with the Kemmis and Mc Taggart Model, consisting of four stages: planning, implementation, observation and reflection. The research results show that through PBL, mathematics learning outcomes increase significantly. The application of concrete object props also succeeded in increasing students' understanding and creativity. Quantitatively, the average score reached 81.48% in cycle II with classical completeness of 100%, showing a significant increase after improving learning. This research makes a positive contribution to class I mathematics learning by utilizing the PBL method and concrete object teaching aids.